The technical-operational dimension in the professional training of social workers - Matos de Figueiredo, Jheninffer Priscila; Nobre Pontes, Reinaldo; Cezar, Karina Camille Marques; Tabaranã Silva, Olga Myrla (Argumentum, 2023)
This work addresses, in an introductory way, the technical-operational dimension within the context of professional training in Social Work. It identifies how prominent the theme is in the scientific output on Social Work in the two most important universities in the Northern region of Brazil, the Federal University of Pará (UFPA) and the Federal University of Amazonas (UFAM). The empirical basis for the analysis is a bibliographical survey (state of the art) carried out in the CAPES database of theses and dissertations. We conclude that this theme is poorly represented in the scientific research published in the area of Social Work and is even scarcer in the postgraduate programmes of the institutions in question, with the greater lack being at the UFPA.